Sarah the gevirah: A comparison of Sarah and the queen mothers, of matriarchs in the dynastic succession of sons and nations - Brewer-Boydston, Ginny (Review and expositor, 2018)
Abraham's and Sarah's struggle to produce a child is the first of the ancient Israelites' struggles to claim the divine promise, individually and collectively. This struggle of the first patriarch and matriarch begins with Sarah's barrenness and her resolve to find other means to produce an heir for Abraham and herself in Genesis 16. The first nine verses refer to Sarah as Hagar's "mistress" or gevirah three times (vv 4, 8, 9). Initially, there is little doubt for the reader to be concerned about any question of terminology concerning the term title as Sarah is the mistress of the servant Hagar. The reader, however, encounters a slight problem when one compares the other texts in which the term appears as it is most frequently applied to the queen mother. What becomes evident when one explores these texts and compares their meanings and contexts is that Sarah's story corresponds to the majority of the contexts of the use of gevirah, where succession of an heir is involved, which is that of the position of the queen mother. In order to demonstrate this similarity, I will first explore Sarah's story where gevirah appears through the securing of her son and Abraham's heir, Isaac, all of which centers around the importance of succession. I will follow the story of Sarah the gevirah with how those women given the title of gevirah also acted in matters of succession. I will conclude with the implication of this comparison, which is that gevirah represents a deliberate choice of terminology as this appellation foreshadows Sarah as the chosen matriarch who will carry the promised heir, and justifies the actions she takes in order to secure the succession of her biological son.